Sedentary behavior and physical activity preferences in patients with knee osteoarthritis: insights from a cross-sectional study - Samya Ez-zaoui; Hanan Rkain; Sara Bahloul; Fatine Kronbi; Rahma Honsali; Sara Farih; Imane Bensghir; Nada Benzine; Hind L’heri; Loubna Lammaghi; Latifa Tahiri; Najia Hajjaj-Hassouni; et al. (Reumatismo)
Objective. Osteoarthritis (OA) is a prevalent condition associated with significant disability, particularly affecting mobility and daily activities. Sedentary behavior is common among individuals with knee OA, influenced by factors such as pain, functional limitations, and sociocultural aspects. Despite the benefits of physical activity in managing knee OA, many patients remain sedentary. Understanding factors contributing to sedentary behavior and patients' preferences regarding physical activity is crucial for effective intervention. This cross-sectional study aimed to assess the level of physical activity among Moroccan patients with knee OA, identify factors associated with sedentary behavior, and explore patients' expectations and preferences regarding physical activity.